A closer look at risk factors for public-private partnerships in Singapore: six case studies. Issue 2 (3rd May 2020) - Kim, Soojin; Kwa, Kai Xiang
ABSTRACT: Despite its global popularity over the past few decades, the public-private partnership (PPP) has not always led to successful outcomes, due largely to a number of risk factors associated with the projects. To explain how and why PPPs sometimes fail, this study considers the success-failure continuum of Singapore's recent PPP experience from 2000 to 2019. After taking a critical, close look at the six failed cases, we identify the following latent risk factors: unstable financial capacity during the execution period of a project, force majeure unforeseen problems that arise, a lack of technical and/or financial foresight, poor corporate management (e.g. delays in construction and poor-quality service delivery), and an unfavourable investment environment stemming from the lack of a clear and supportive governance framework. In addition, we find that most risk factors tend to appear during the contract management (pre-operation) and project management (operation) phases. Such risks seem to drive the operational failure and subsequent contract termination of multiple unsuccessful PPPs, simultaneously (and sometimes sequentially) rather than in isolated fashion. All in all, this study offers for policymakers that better risk allocation and proper, mutual coordination between the public and private partners represent essential factors for PPP success.